New species and newly recorded species of the genus Agonopterix Hübner, [1825] (Lepidoptera: Depressariidae) from China - Zhu, Xiaoju; Zhang, Li; Wang, Shuxia (Zootaxa, 2023)
Thirteen new species of the genus Agonopterix Hübner are described: A. basinigra sp. nov., A. cochleata sp. nov., A. epunctata sp. nov., A. foliiformis sp. nov., A. gibbosa sp. nov., A. hypodroma sp. nov., A. introrsa sp. nov., A. magnimacularis sp. nov., A. nephimacula sp. nov., A. nivimacularis sp. nov., A. parallela sp. nov., A. simipullella sp. nov. and A. sphaeroidea sp. nov. and ten species are recorded for the first time from China: A. abditella Hannemann, 1959, A. angelicella (Hübner, 1813), A. arctica (Strand, 1902), A. arenella (Denis & Schiffermüller, 1775), A. bipunctosa (Curtis, 1850), A. broennoeensis (Strand, 1920), A. kaekeritziana (Linnaeus, 1767), A. kirgizella Lvovsky, 2001, A. ochrocephala Saito, 1980 and A. septicella (Snellen, 1884). Images of both adults and genitalia are provided.